DESIGN OF DOLPHIN STRUCTURE FOR CPO TERMINAL IN MONANO, GORONTALO UTARA - Diar Fathurrohman NIM 15513070, Muhammad
Indonesia is the biggest crude palm oil (CPO) producer country in the world. In Gorontalo Province, there will be additional land for CPO production. Therefore, Terminal for CPO loading and unloading in Gorontalo Province will be built in Monano, Gorontalo Utara. The structure that will be created is dolphin structure. The final project scope included: the explanation of the criteria of design structure, loads calculation on structure, determination of the structure dimension, analysis of the dolphin structure, design of reinforcement of the elements structural, and analysis of soil bearing capacity. General design reference was obtained from the British Standard. While, design criteria for structural elements is using SNI 1729: 2012 for steel and SNI 2847: 2013 for concrete. The structure was designed consists of four structures, loading platform, berthing dolphin, mooring dolphin, and trestle. Structural analysis was done using SAP2000. From the analysis, the value of UCR was 0.831 for the loading platform pile, 0.891 for berthing dolphin pile, 0.91 for mooring dolphin pile, and 0.84 for trestle pile. Then, the output of fixed joint reaction was 939.48 kN for platform loading, 1687.48 kN for berthing dolphin, 1210.61 kN for mooring dolphin, and 795.75 kN for trestle. Thus, the pile was set up to a depth of 16 meters for the platform loading structure, 30 meters for berthing dolphin structure, 34 meters for mooring dolphin structure, and 14 meters for trestle structure. The depth of the pile staked was calculated from mudline.